CHEMICAL HYDROLYSIS, INSILICO PHYSICOCHEMICAL PROPERTIES AND IN-VIVO PHARMACOLOGICAL EVALUATION OF ANTIDIABTIC AND ANTIHYPERTENSIVE CODRUGS - Andhale, Ganesh Sakharam (Asian Journal of Pharmaceutical Research and Development, 2018)
In the present research work codrugs of Propranolol and Metoprolol with Metformin were synthesized with an aim of improving the biological activity and to check the effectiveness of release of the parent drugs in presence of spacer. Ester prodrugs of Propranolol and metoprolol were synthesized by using succinic, maleic, pthalic anhydride and substituted derivatives of them. The resulted prodrugs were converted into codrugs (CO1-6) by reacting with Metformin. The compounds were characterized by melting point, FT-IR, 1H-NMR and mass spectroscopy. The chemical hydrolysis of CO1-6 was carried out at the pH 1.2, 6.8 and 7.4. Almost all compounds showed encouraging chemical stability at pH 1.2 and 6.8 whereas showed the moderate hydrolysis at pH 7.4 but codrug CO4 didn’t showed hydrolysis at any pH condition. Further codrugs were screened for antihypertensive and antidiabetic activity by simultaneous induction of two-kidney, one clip renal hypertension and STZ-induced diabetic model in wistar rats. The spacer containing dipropyl maleate codrugs (CO3 and CO6) showed longer duration of action. The current paper also describes about the molecular properties evaluation of the synthesized codrugs.